Endothelial cells under disturbed flow release extracellular vesicles to promote inflammatory polarization of macrophages and accelerate atherosclerosis - Zhe Hou; Li Deng; Fei Fang; Ting Zhao; Yaojia Zhang; Gang Li; Michael Z. Miao; Yongcang Zhang; Hongchi Yu; Xiaoheng Liu (BMC Biology)
Abstract Background Extracellular vesicles (EVs) derived from endothelial cells (ECs) are increasingly recognized for their role in the initiation and progression of atherosclerosis. ECs experience varying degrees and types of blood flow depending on their specific arterial locations. In regions of disturbed flow, which are predominant sites for atherosclerotic plaque formation, the impact of disturbed flow on the secretion and function of ECs-derived EVs remains unclear. This study aims to assess the role of disturbed flow in the secretion of EVs from ECs and to evaluate their proatherogenic function. Results Our comprehensive experiments revealed that disturbed flow facilitated the secretion of ECs-derived EVs both in vivo and in vitro. Mechanistically, the MAPK pathway transduces mechanical cues from disturbed flow in ECs, leading to increased secretion of EVs. Pharmacological inhibition of the MAPK pathway reduced the secretion of EVs even under disturbed flow conditions. Interestingly, under disturbed flow stimulation, ECs-derived EVs promoted monocyte accumulation and enhanced their invasion of the endothelium. More important, these EVs initiated the inflammatory polarization of macrophages from the M2 to the M1 phenotype. However, the phenotypic switching of vascular smooth muscle cells was not affected by exposure to these EVs. Conclusions Taken together, targeting the MAPK signaling pathway holds potential as a novel therapeutic strategy for inhibiting the secretion of EC-derived EVs and mitigating the inflammatory polarization of macrophages, ultimately ameliorating the progression of atherosclerosis. Graphical Abstract